The impact of military service on health and well-being. (31st October 2018) - Williamson, V; Diehle, J; Dunn, R; Jones, N; Greenberg, N
Abstract: Background: While it is known that some UK Armed Forces (UK AF) personnel and veterans experience physical and mental health problems, the possible future healthcare needs of military veterans are unknown. Aims: To estimate the number of military personnel who may experience physical and/or psychological health problems associated with their military service. Methods: Data were obtained via Freedom of Information requests to several sources, including Defence Statistics. Raw data from research studies were also used where available. Data were analysed using meta-analytic methods to determine the rate of physical, mental or comorbid health problems in AF personnel. Results: Musculoskeletal problems were the predominant reason for medical discharge from service. In terms of mental health, meta-analyses estimated that veteran reservists (part-time military members) previously deployed to operational areas had the highest proportion of general health problems (35%), previously deployed veteran regulars (those in full time military employment) and veteran reservists had the highest proportion of post-traumatic stress disorder (9%), and regular personnel with a deployment history had the highest proportion of alcohol problems (14%). Overall, our findings suggest that at least 67515 veterans are likely to suffer from mental and/or physical health problems at some point as a result of their service between 2001 and 2014. Conclusions: The results of this study highlight that the difficulties personnel may face are largely musculoskeletal or mental health-related. These findings may help with planning the provision of future physical and mental health care and support for those who serve in the UK AF.